Analisis Biaya Perawatan Pasien Stroke di Rumah Sakit Royal Prima Tahun 2020 - Panta Leon Raynard Aditia Kaban; Chrismis Novalinda Ginting; Sri Wahyuni Nasution (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the cost of illness stroke in patients treated at RSU Royal Prima Medan—this partial economic evaluation research with a retrospective approach using secondary data. The results of this study indicate that the direct medical cost of a stroke at RSU Royal Prima Medan reached IDR 2,403,132,163, and the direct non-medical price reached IDR 809,484,699, with a range of charges billed to patients between IDR 3,832,436 to IDR 142,986,392 and duration of hospitalization between 1 and 25 days of hospitalization. In conclusion, the average cost of illness for stroke at RSU Royal Prima Medan reached Rp. 20,861,148 ± Rp. 22,880,177 per episode per patient with an average stay of 6.45 ± 3.40 days. Keywords: Cost of Illness, Direct Cost, Hospitalization, Stroke